On the Solvability of the Hele–Shaw Model Problem in Weighted Hölder Spaces in a Plane Angle - Bazalii, B. V.; Vasil'eva, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We study a nonstationary boundary-value problem for the Laplace equation in a plane angle with time derivative in a boundary condition. We obtain coercive estimates in weighted Hölder spaces.